(untitled) (Ágora de Heterodoxias, 2021)
The Sustainable Development Goals are a planning and monitoring tool for most countries, since they constitute a guide to advance towards a sustainable, inclusive and harmonious development with the environment, through the implementation of public policies and the participation of all sectors of society. Therefore, this research aims to develop a mapping of good practices for compliance with these by Mexican companies located in a municipality in the state of Sonora, Mexico. To achieve this, a random sample of 379 MSMEs and a methodology with a quantitative approach, descriptive and transactional design were used. The instrument evaluated the dimensions of society, prevention, environment and, economy. The data was analyzed in a descriptive and multivariate way and the degree of satisfaction was measured based on compliance with the policies inherent to sustainable development. The results show that the cause that has hindered the implementation of the Sustainable Development Goals in companies has been the lack of more effective monitoring strategies in business and institutional management, in order to facilitate access and promote information related to the 2030 Agenda